Geomagnetically trapped, albedo and solar energetic particles: Trajectory analysis and flux reconstruction with PAMELA. Issue 4 (15th August 2017) - Bruno, A.; Adriani, O.; Barbarino, G.C.; Bazilevskaya, G.A.; Bellotti, R.; Boezio, M.; Bogomolov, E.A.; Bongi, M.; Bonvicini, V.; Bottai, S.; Cafagna, F.; Campana, D.; et al.
Abstract: The PAMELA satellite experiment is providing comprehensive observations of the interplanetary and magnetospheric radiation in the near-Earth environment. Thanks to its identification capabilities and the semi-polar orbit, PAMELA is able to precisely measure the energetic spectra and the angular distributions of the different cosmic-ray populations over a wide latitude region, including geomagnetically trapped and albedo particles. Its observations comprise the solar energetic particle events between solar cycles 23 and 24, and the geomagnetic cutoff variations during magnetospheric storms. PAMELA's measurements are supported by an accurate analysis of particle trajectories in the Earth's magnetosphere based on a realistic geomagnetic field modeling, which allows the classification of particle populations of different origin and the investigation of the asymptotic directions of arrival.